Pelatihan Pemberdayaan Perempuan Untuk Mendorong Partisipasi Perempuan Pada Aspek Pembangunan (Ekonomi, Politik, Dan Sosial) Dalam Upaya Pengimplementasian SDGs (Sustainable Development Goals) Di Kampung Nelayan Seberang Belawan - Srifauzi, aulia; Fajrina, Siti; Ardiansyah, Yuda; Panggabean, Febri Monalisa (LPPM Universitas Potensi Utama, 2024)
Implementing the Sustainable Development Goals (SDGs) is critical to preventing gender inequality and increasing political participation. These goals require governments and communities to strengthen gender equality and empower women through public policy, legislation, and gender mainstreaming. The role of women is very important in development, both from an economic, political, and social perspective. To address inequality in the financial and political spheres, efforts involving all sectors of life and community participation are needed. Communities play a key role in changing the view that women are unnecessary in economic, social, and political involvement, especially in coastal areas. Therefore, we held training in Kampung Nelayan Seberang Belawan, far from the city center, to discuss with the community the importance of women's participation in development. This training is expected to help the people of Kampung Nelayan Seberang understand the importance of women's role in development (economic, political, social). This abdimas activity is useful for students, lecturers, the University, and the community to provide knowledge so that international relations study programs can be useful in the community. It is hoped that the people of Kampung Nelayan Seberang can take advantage of this activity to consider community participation in the development field (economic, political, social